Atmospheric Turbulence Effects on Wind Turbine Wakes over Two-Dimensional Hill: A Wind Tunnel Study - Bowen Yan; Shuangchen Tang; Meng Yu; Guowei Qian; Yao Chen (Energies)
The wake behavior of wind turbines in complex terrain is influenced by the combined effects of atmospheric turbulence and terrain features, which brings challenges to wind farm power production and safety. Despite extensive studies, there remains a gap in understanding the combined impact of turbulent inflows and terrain slopes on turbine wake behaviors. To address this, the current study conducted systematic wind tunnel experiments, using scaled wind turbines and terrain models featured both gentle and steep slopes. In the experiments, different turbulent inflows were generated and the wake characteristics of turbines located at different locations were analyzed. The results demonstrated that higher turbulence intensity accelerates wake recovery, and that steep slopes introduce distinctive wake patterns, including multi-peak added turbulence intensity profiles. Moreover, turbines on hilltops exhibited a more rapid wake recovery compared to those positioned in front of hills, a phenomenon attributed to the influence of adverse pressure gradients. This study provides pivotal experimental insights into the evolution laws of wind turbine wake over terrains under different turbulent inflow conditions, which are instrumental in wind turbine siting in complex terrains.